M-Umrah application development for smart phone - Aziz, Amir (2013)
This project is developed to help muslim people when they want to perform umrah. The umrah mobile application (m-Umrah) contains information on umrah from the beginning of umrah which is to set the intention or niat until last phase of umrah which is order. Before this, people always use book as their guideline when they are performing umrah and this can cause discomfort to them. A part from that, based on the preliminary study it is found that the gaming application is the most used application compared to the religion mobile application. The methodology that will be used in this project is the ADDIE model. From the model, the data collected from the data analysis phase and at the end of the phase a full functional application will be produced. With this application, hopefully it will help them when they are performing the umrah based on its handiness and user friendly feature. For future recommendation, it is hope that the hajj content will be included inside the application.